Pengaruh Permainan Tradisional Engklek Terhadap Perkembangan Motorik Kasar Anak Usia 5-6 Tahun di Paud Anakkonhi Do Hamoraon di Ahu (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
The purpose of this research is to know influence of traditional engklek games on gross motoric development of children aged 5-6 years in early childhood education anakhonhi do hamoraon di ahu. The method used in this research is a quantitative research method with type study pre-experimental design type one shot case study . The population is all children Aged 5-6 Years in Early Childhood Education Anakhonhi Do Hamoraon di Ahu Sisordak Village Subdistrict Parmonangan in total 30 people. Data is collected by item observation closed positive as many as 30 items. The results of the data analysis show that there is an influence of the game traditional crank to development motor rough child ages 5-6 years in early childhood education Anakhonhi Do Hamoraon Di Ahu : 1) Analysis requirements test: a) a positive relationship test obtained r xy = 0.565 > r table ( a = 0.05, n = 17 ) = 0. 482 Thus it is known that there is a positive relationship between variable X and variable Y. b) A significant relationship test is obtained by tcount = 2.651 > ttable ( a = 0.05, dk = n-2 = 15 ) = 2, 131 thus there is a significant relationship between variable X and variable Y. 2) Influence test: Test the regression equation, the regression equation Y ̂="7.10"+0.85X is obtained. Testing the hypothesis using the F test obtained Ftable=(a=0.05, dk quantifier k=13, dk denominator=n-2=17-2=15) = 2.40 then Fcount > Ftable which is 7.03 > 2, 40.Thus Ha accepted and H0 rejected.